Pengaruh Pengembangan Karir dan Perencanaan SDM Terhadap Kinerja Karyawan Melalui Motivasi Kerja Sebagai Variabel Intervening Pada Diperon Kelapa Sawit Brama Kumbara Pasaman Barat - Lutfia Lutfia; Addina Hayati Akilie; Siti Medira; Chintya Ones Charli (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2024)
This article discusses a literature review of factors that have an impact on employee performance, namely work motivation as an intervening variable, career development, and HR planning. The purpose of writing this research is to determine the hypothesis that impacts each variable so that it can be used for further research. This research provides explanation if: 1) HR planning has a positive or meaningful influence on work motivation; 2) HR development has a positive and meaningful influence on work motivation. 3) HR planning has a positive and meaningful influence on employee performance; 4). HR development has a positive and meaningful influence on employee performance; 5). Work motivation has a positive and meaningful impact on employee performance. 6). Work motivation can mediate HR planning which has an impact on employee performance,